2002
DOI: 10.1210/jcem.87.7.8697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Hybridization Analysis of Adrenocortical Tumors

Abstract: Comparative genomic hybridization (CGH) is a molecular cytogenetic technique that allows the entire genome of a tumor to be surveyed for gains and losses of DNA copy sequences. A limited number of studies reporting the use of this technique in adult adrenocortical tumors have yielded conflicting results. In this study we performed CGH analysis on 13 malignant, 18 benign, and 1 tumor of indeterminate malignant potential with the aim of identifying genetic loci consistently implicated in the development and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 38 publications
0
36
0
10
Order By: Relevance
“…As reported by Dohna et al, gains and high-level amplifications in chromosomes 7, 14, and 19 were seen only in ACC and not in benign adrenocortical neoplasms, suggesting that these events may be late genetic perturbations in tumorigenesis (16). Deletions have also been found within chromosomes 1p and 17p implicating potential losses of tumor suppressor genes in these regions, marking the progression of benign adrenal adenoma to ACC (17). Similar to other cancers, there is evidence that the number of genetic aberrations increases as a factor of tumor growth and this size progression has been correlated with malignancy (14,18,19).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…As reported by Dohna et al, gains and high-level amplifications in chromosomes 7, 14, and 19 were seen only in ACC and not in benign adrenocortical neoplasms, suggesting that these events may be late genetic perturbations in tumorigenesis (16). Deletions have also been found within chromosomes 1p and 17p implicating potential losses of tumor suppressor genes in these regions, marking the progression of benign adrenal adenoma to ACC (17). Similar to other cancers, there is evidence that the number of genetic aberrations increases as a factor of tumor growth and this size progression has been correlated with malignancy (14,18,19).…”
Section: Introductionmentioning
confidence: 56%
“…Genes within these regions can give insight into the pathways of oncogenesis active within ACC. Among other deleted regions, literature suggests that the loss of chromosomes 1p and 17p are linked to progression from benign to malignant ACC (17). Recent studies have identified a chromodomain helicase DNAbinding protein 5 within 1p36.31 as a tumor suppressor gene (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of these gene sets are presented in Table 3. Cytogenetic (CGH and FISH) data on adrenocortical tumours were acquired from 10 publications found by literature search (Kjellman et al, 1996;Figueiredo et al, 1999Figueiredo et al, , 2005Russell et al, 1999;Zhao et al, 1999Zhao et al, , 2002Dohna et al, 2000;Sidhu et al, 2002;Bertherat et al, 2003;Stephan et al, 2008). These included 87 ACA and 124 ACC samples (Supplementary Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…A análise do modelo de inativação do cromossomo X em heterozigose em células somáticas femininas demonstrou que carcinomas derivam de células monoclonais enquanto adenomas têm origem tanto monoclonal quanto policlonal (32). Por meio de técnicas de hibridização genômica comparativa (HGC), alterações com ganho nos cromossomos 4, 5, 12, 19 e perdas em 1p, 17p, 22p, 11q, 2q e 11q foram identificadas em 61% dos adenomas e em 62% dos carcinomas (33). Estudos usando marcadores de microssatélites identificaram perda da heterozigose (LOH) em carcinomas nas regiões 11q13 (>90%), 17p13 (>85%) e 2p16 (92%) (28,34).…”
Section: Bases Moleculares Dos Tumores Adrenocorticaisunclassified